Business Model Canvas: The Implementation Method of Corporate Social Entrepreneurship - Hani Sirine; Yustina Ertie Pravitasmara Dewi (Universitas Warmadewa, 2022)
Corporate social responsibility (CSR) is entrepreneurs’ obligation to be socially responsible so as to create values for the community, one of which is through social entrepreneurship. The CSR and social entrepreneurship form a corporate social entrepreneurship which can strategically provide a balance between the economic value and social value among various stakeholders. This study aims to determine stages of implementation of corporate social entrepreneurship and development of Business Model Canvas to run the corporate social entrepreneurship in Sido Muncul partnership program with Parang Gupito Farmer Group. The results show that the stages of implementation of corporate social entrepreneurship in Sido Muncul partnership program in Parang Gupito include problem identification and need analysis, resource allocation and coordination, network building, intensive mentoring, sustainable innovation, getting business partners, and performance assessment. The value proportion of the Sido Muncul partnership program in the Business Model Canvas for the Parang Gupito Farmer Group includes knowledge and skills about agriculture, agricultural product innovation, marketing and distribution, tourism services, product standardization, as well as price and market guarantee that have an impact on increasing the farmers’ welfare.